The Causal Relationship between Plasma Myeloperoxidase Levels and Respiratory Tract Infections: A Bidirectional Mendelian Randomization Study - Xiu Liu; Chuchu Zhang; Jiajia Ren; Guorong Deng; Xi Xu; Jueheng Liu; Xiaoming Gao; Ruohan Li; Jiamei Li; Gang Wang (Mediators of Inflammation)
Background. Observational researches reported the underlying correlation of plasma myeloperoxidase (MPO) concentration with respiratory tract infections (RTIs), but their causality remained unclear. Here, we examined the cause–effect relation between plasma MPO levels and RTIs. Materials and Methods. Datasets of plasma MPO levels were from the Folkersen et al. study (n = 21,758) and INTERVAL study (n = 3,301). Summarized data for upper respiratory tract infection (URTI) (2,795 cases and 483,689 controls) and lower respiratory tract infection (LRTI) in the intensive care unit (ICU) (585 cases and 430,780 controls) were from the UK Biobank database. The primary method for Mendelian randomization (MR) analysis was the inverse variance weighted approach, with MR-Egger and weighted median methods as supplements. Cochrane’s Q test, MR-Egger intercept test, MR pleiotropy residual sum and outliers global test, funnel plots, and leave-one-out analysis were used for sensitivity analysis. Results. We found that plasma MPO levels were positively associated with URTI (odds ratio (OR) = 1.135; 95% confidence interval (CI) = 1.011–1.274; P=0.032) and LRTI (ICU) (OR = 1.323; 95% CI = 1.006–1.739; P=0.045). The consistent impact direction is shown when additional plasma MPO level genome-wide association study datasets are used (URTI: OR = 1.158; 95% CI = 1.072–1.251; P<0.001; LRTI (ICU): OR = 1.216; 95% CI = 1.020–1.450; P=0.030). There was no evidence of a causal effect of URTI and LRTI (ICU) on plasma MPO concentration in the reverse analysis (P>0.050). The sensitivity analysis revealed no violations of MR presumptions. Conclusions. Plasma MPO levels may causally affect the risks of URTI and LRTI (ICU). In contrast, the causal role of URTI and LRTI (ICU) on plasma MPO concentration was not supported in our MR analysis. Further studies are needed to identify the relationship between RTIs and plasma MPO levels.